2021
DOI: 10.4103/jcd.jcd_642_20
|View full text |Cite
|
Sign up to set email alerts
|

Root anatomy and canal configuration of human permanent mandibular second molar: A systematic review

Abstract: The objective of the study was to review the literature on root anatomy and canal configuration in permanent mandibular second molar based on Vertucci classification. Online electronic databases such as PubMed-Medline, Embase, Scopus, and Cochrane Library were searched using appropriate keywords from the earliest available date till 10 th February 2021 restriction on language. Additional sources such as Google Scholar, major journals, unpublished studies, conference proceedings, and cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
(262 reference statements)
0
2
0
Order By: Relevance
“…In this study, we investigated the configuration of root canals in immature permanent teeth. The configuration of the root canal with complete root development has been extensively reviewed in the existing literature [13,[24][25][26]. Root canals can exhibit several different shapes in cross-section: round, oval, long-oval, ribbon-shaped or irregular [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the configuration of root canals in immature permanent teeth. The configuration of the root canal with complete root development has been extensively reviewed in the existing literature [13,[24][25][26]. Root canals can exhibit several different shapes in cross-section: round, oval, long-oval, ribbon-shaped or irregular [27].…”
Section: Discussionmentioning
confidence: 99%
“…An excellent knowledge of root anatomy is also an important factor when performing endodontic procedures. This is because root morphology can vary depending on age, population, ethnicity and the choice of research method [13]. Research has shown that persistent root canal infection is the primary reason for treatment failure [14].…”
Section: Introductionmentioning
confidence: 99%